The Decision Making Individual Differences Inventory and guidelines for the study of individual differences in judgment and decision-making research - Kirstin C. Appelt; Kerry F. Milch; Michel J. J. Handgraaf; Elke U. Weber (Judgment and Decision Making, 2011)
Individual differences in decision making are a topic of longstanding interest, but often yield inconsistent and contradictory results. After providing an overview of individual difference measures that have commonly been used in judgment and decision-making (JDM) research, we suggest that our understanding of individual difference effects in JDM may be improved by amending our approach to studying them. We propose four recommendations for improving the pursuit of individual differences in JDM research: a more systematic approach; more theory-driven selection of measures; a reduced emphasis on main effects in favor of interactions between individual differences and decision features, situational factors, and other individual differences; and more extensive communication of results (whether significant or null, published or unpublished). As a first step, we offer our database—the Decision Making Individual Differences Inventory (DMIDI; http://html://www.sjdm.org/dmidi), a free, public resource that categorizes and describes the most common individual difference measures used in JDM research.